(untitled) (Research, Society and Development, 2021)
Objective: To analyze the muscle strength and functionality of hospitalized patients admitted for respiratory conditions. Methodology: Cross-sectional study, carried out in patients diagnosed and hospitalized with respiratory diseases. The assessments were performed using the Medical Research Council (MRC), Functional Independence Measure (MIF), World Health Disability Assessment Schedule (WHODAS), manovacuometry and dynamometry in patients admitted to Hospital University Student of Lagarto. Results: 97 patients participated in the respective study, where a reduction in peripheral and respiratory muscle strength was observed. When analyzing functionality, moderate functional difficulty was noted, both instruments being correlated (r= -722; p<0.01). By analyzing the relationship between mean MRC (MMSS) and Palmar Grip Force D and E, it was demonstrated that there was a high and positive correlation (p<0.01) between them. There was a high positive correlation (p<0.01) between MRC and MIF, and a high and negative correlation with WHODAS (r= -598; p<0.01). When evaluating the averages of Palmar Grip Force and MRC between the groups over 60 years and under 60 years, it was found that the age factor contributes to the loss of muscle strength and, consequently, of functionality (p = 0.000). Conclusion: Patients hospitalized due to acute or acute chronic respiratory diseases presented reduced peripheral and respiratory muscle strength. This reality highlights the importance of early physical therapy assistance, based on functionality and muscle strength gain in these patients.